PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG PADA FINANCIAL INSTITUTION - Heru Harmadi Sudibyo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to evaluate and determine the effect of Profitability and Company Size on Audit Report Lag in Financial Institutional sub sector companies listed on the Indonesia Stock Exchange from 2014 to 2018. This study uses secondary data and uses purposive sampling with predetermined criteria. The sample of this study uses 13 companies engaged in the Financial Institutional sub sector that have been listed on the Indonesia Stock Exchange for the period 2016 to 2020. The analytical technique used in this study uses multiple linear regression analysis and uses the Eviews version 9 application. The results of this study indicate that Profitability and Company Size have a significant and simultaneous effect on Audit Report Lag. With a coefficient of determination of 0.870044, this states that the independent variable explains the dependent variable 87%. And the remaining 13% id influenced by other independent variables outside of this study.